Simulasi Proses Bisnis Pondok Pesantren Menggunakan Anylogic Berdasarkan Metode Business Process Improvement (BPI) - Rizqi, Nikmatur; Hidayati, Ulfa; Ramadhan, Teguh Arief; Yaqin, M. Ainul (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
Islamic boarding schools are traditional Islamic educational institutions in which religious values are taught as guidelines to be applied in everyday life. Islamic boarding schools are also analogous to enterprise in which there must be a business process to achieve the objectives of the establishment of boarding schools themselves. The design of business processes in Islamic boarding schools may be able to produce the desired results but sometimes it is not in accordance with the desired costs or desired time. These problems can be overcome by running a business process simulation, which aims to help the analysis and understanding of business process models. Anylogic is used in this study to simulate the boarding school business processes and use the Business Process Improvement (BPI) method to analyze problems in business processes and methods BPMN (Business Process and Notation Model) as a tool to describe or create business process flow models in graphical form.